In the footsteps of P. Žostautaitė? (About the defense of lngrida Jakubavičienė Doctoral Dissertation "Nacionalistic Activities of Lithuanian Germans in the 3rd and 4rd Decades of the 20th Century) - Tadas Tumėnas (Lietuvos Istorijos Studijos)
-